Coronavirus (Covid- 19) Anxiety level among General Education Diploma students in Asharqia South Governorate in Oman - Al-Khawaja, Abdul Fattah Mohammed Saeed; Alhasani, Issa Saleh Hamed; Alsawai, Faisal Khalfan Khamis (Journal of Educational and Psychological Sciences, 2020)
The present study aimed to investigate Coronavirus (Covid- 19) anxiety level among General Education Diploma students in South Governorate in Oman, based on a sample of 848 students (250 male students, 598 female students) during the second semester 2020. Descriptive method was used. Findings show that there is an increase in anxiety level of among the sample, where it reached (4.24). Also, Findings show that there is a significant difference in anxiety level according to gender (male-female). The study also showed significant differences in Anxiety level according to the variable of the educational path (scientific (pure)- literary (applied)) in the dimension (personal anxiety) & (media anxiety) in favor of students of the literary path (applied), & in the dimension (personal anxiety) in favor of low academic students. The study recommends intensifying psychological counseling and vocational guidance programs with the available means to alleviate students' anxiety, and conducting studies that include the study variable on other groups of students.
Keywords: Coronavirus; Coronavirus (Covid- 19) Anxiety; Coronavirus (Covid- 19) Anxiety & General Education Diploma students at Sultanate of Oman.; General Education Diploma students at Sultanate of Oman